Curcumin supplementation positively modulates fatty acid profiles in lamb meat - Marcon H.* (2020)
© 2020 Elsevier B.V.Modulation of fatty acid content in meat is thought to be a primary approach to increase human consumption of healthy fatty acids, including polyunsaturated fatty acids (PUFAs). Recently, curcumin has been used to enhance PUFA content, as well as to reduce the content of saturated fatty acids (SFAs) in egg yolk and milk; nevertheless, its effects on meat remains unknown. Therefore, the aim of this study was to determine whether curcumin supplementation in the concentrate of post-weaning lambs would influence fatty acid profiles in their meat. Thirty-two Lacaune lambs fed on a corn silage-based diet were divided into in four groups with four repetitions each and two lambs per repetition, as follows: curcumin-supplemented animals received concentrate containing 100 mg kg−1 (T100), 200 mg kg−1 (T200) and 300 mg kg−1 (T300) of curcumin, while the other group (control; T0) received the same concentrate without curcumin. No significant differences were observed between groups regarding body weight on all evaluated days, while average daily weight gain was significantly higher in group T300 than in T0. Total fat in meat was significant lower in groups T200 and T300 than in group T0. Total SFAs were significant lower in group T300 than in T0, while total PUFAs were higher. No significant difference was observed between groups with respect to total monounsaturated fatty acids (MUFA). Based on this evidence, we conclude that 300 mg curcumin/kg enhances daily weight gain. This supplement improves the fatty acid profiles in meat via reduction of SFAs and augmentation of PUFAs. Both effects are positive in terms of human health.